Sarcopenic Obesity in Facioscapulohumeral Muscular Dystrophy - Vera, Kathryn; McConville, Mary; Kyba, Michael; Keller-Ross, Manda (Frontiers in Physiology, 2020)
Background: Sarcopenic obesity has been observed in people with neuromuscular impairment, and is linked to adverse health outcomes. It is unclear however, if sarcopenic obesity develops in adults with facioscapulohumeral muscular dystrophy (FSHD). Methods: The purpose of this study was to determine if adults with FSHD meet criteria for sarcopenic obesity (appendicular lean mass index (ALMI) scores of <7.26 kg/m2 or 5.45 kg/m2; % fat mass (FM) 28% or 40% in men/women). Ten people with FSHD (5011 years, 2 females) and ten age/sex-matched controls (4713 years, 2 females) completed one visit, which included a full-body dual-energy x-ray absorptiometry (DXA) scan. Regional and whole body total mass, fat mass (FM), and lean mass (LM) were collected and body mass index (BMI) and sarcopenia measures were computed. Results: People with FSHD and controls had a similar whole body total mass (84.512.9 vs. 81.813.5 kg, respectively; p=0.65). Though BMI was 2% lower in the FSHD group (p=0.77), the % FM was 46% higher in FSHD, compared with controls (p<0.01). In addition, ALM volume was 23% lower (p=0.02) and ALMI was 27% lower in FSHD compared with controls (p<0.01). Whole body LM trended to be lower in FSHD vs. controls (p=0.05), and arm and leg LM were both lower in FSHD compared with controls (p<0.05). Furthermore, the % LM was 18% lower in FSHD vs. controls (p<0.01). FSHD participants exhibited greater total body FM (p<0.01) and total leg FM (p<0.01), but were similar in volume of total arm FM compared with controls (p=0.09). Conclusions: Findings from this study suggest that people with FSHD, although similar in BMI and total body mass compared with controls, commonly meet the definition of sarcopenic obesity. Adults with co-existing FSHD and sarcopenic obesity may be at risk for significant impairments in quality of life, and encounter additional challenges in the management of FSHD manifestations.